2022
DOI: 10.3390/toxins14070430
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Turmeric Powder on Aflatoxin M1 and Aflatoxicol Excretion in Milk from Dairy Cows Exposed to Aflatoxin B1 at the EU Maximum Tolerable Levels

Abstract: Due to the climatic change, an increase in aflatoxin B1 (AFB1) maize contamination has been reported in Europe. As an alternative to mineral binders, natural phytogenic compounds are increasingly used to counteract the negative effects of AFB1 in farm animals. In cows, even low dietary AFB1 concentrations may result in the milk excretion of the genotoxic carcinogen metabolite aflatoxin M1 (AFM1). In this study, we tested the ability of dietary turmeric powder (TP), an extract from Curcuma longa (CL) rich in cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 50 publications
0
31
0
Order By: Relevance
“…It is reported that clay products have not consistently prevented decreases in milk yield caused by AFB1 ingestion, and yeast fermentation products have been reported to have potential to improve animal performance parameters [ 42 ]. More recent studies have focused on the combined application of clays and yeast [ 17 , 24 , 42 , 44 , 45 , 46 , 67 ] or the use of natural compounds, particularly phytogenic compounds, such as curcumin and curcuminoids from turmeric powder [ 68 ]. A short summary of the reviewed studies is provided in Appendix A .…”
Section: Main Factors Influencing Aflatoxin Carry-overmentioning
confidence: 99%
See 1 more Smart Citation
“…It is reported that clay products have not consistently prevented decreases in milk yield caused by AFB1 ingestion, and yeast fermentation products have been reported to have potential to improve animal performance parameters [ 42 ]. More recent studies have focused on the combined application of clays and yeast [ 17 , 24 , 42 , 44 , 45 , 46 , 67 ] or the use of natural compounds, particularly phytogenic compounds, such as curcumin and curcuminoids from turmeric powder [ 68 ]. A short summary of the reviewed studies is provided in Appendix A .…”
Section: Main Factors Influencing Aflatoxin Carry-overmentioning
confidence: 99%
“…Cha et al (2021) [ 24 ] experienced significantly lower milk AFM1 concentrations and AFB1-AFM1 transfer rates (0.57% and 0.63% compared to 1.16%) when a montmorillonite-diatomite based patented adsorbent and a montmorillonite, diatomite, yeast cell wall and sodium-alginate-based adsorbent were fed to cows in addition to an aflatoxin challenge. In one of the most recent works, Girolami et al (2022) [ 68 ] studied the effects of curcumin and curcuminoids from turmeric powder on the carry-over of aflatoxins. Beneficial effects had previously been demonstrated with this substance in vitro and in other food-producing species, including ruminants.…”
Section: Appendix A1 Activated Carbons and Hscasmentioning
confidence: 99%
“…Aflatoxins are metabolites of Aspergillus flavus Link ex Fries, a fungus that under certain conditions, grows prolifically on peanuts, cereals, and milk produced by cows [ 1 , 2 ]. AFB 1 is the most carcinogenic of the aflatoxins (aflatoxin B 2 (AFB 2 ), aflatoxin G 1 (AFG 1 ), and aflatoxin G 2 (AFG 2 ); aflatoxin B 1 (AFB 1 , Figure 1 ) [ 3 ]).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, climate change is predicted to worsen the maize contamination in Europe [ 31 ]. The use of different compounds able to bind AFB1 to reduce its bioavailability was purposed, but this approach is not totally effective and implies side effects [ 32 , 33 ]. A biocontrol formulation comprised on an AF- A. flavus strain, AF-X1, was successfully developed to address the contamination in commercially grown maize in Italy.…”
Section: Introductionmentioning
confidence: 99%